+0  
 
0
38
1
avatar+257 

If f(x)=g(g(x))-g(x) and g(x)=2x-1, find f(3).

 

Thats my last question for now... Thanks for all the help!

AnonymousConfusedGuy  Nov 30, 2017
Sort: 

1+0 Answers

 #1
avatar+79846 
+1

Let's first find  g (g(x)) 

 

This is literally putting g(x)  into the x in  g(x)....so we have.... 

 

2 [ 2x - 1]  -  1    =    4x - 3

 

So  

 

g (g(x))  - g (x)   =

 

[ 4x - 3 ] - [ 2x  - 1 ]  =

 

2x  - 2    =  f(x)

 

So

 

f(3)   =  2(3) - 2     =   4

 

 

cool cool cool

CPhill  Nov 30, 2017

7 Online Users

avatar
We use cookies to personalise content and ads, to provide social media features and to analyse our traffic. We also share information about your use of our site with our social media, advertising and analytics partners.  See details